2020
DOI: 10.3389/fvets.2020.564795
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impacts of Liver Fluke on Livestock Farms Under Climate Change–A Farm Level Assessment

Abstract: Liver fluke infection (fascioliasis) is a parasitic disease which affects the health and welfare of ruminants. It is a concern for the livestock industry and is considered as a growing threat to the industry because changing climatic conditions are projected to be more favorable to increased frequency and intensity of liver fluke outbreaks. Recent reports highlighted that the incidence and geographic range of liver fluke has increased in the UK over the last decade and estimated to increase the average risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The FEPM is a modified version of ScotFarm, a farm level economic model developed at SRUC to conduct impact assessment of external shocks to an agricultural production system. The ScotFarm model has previously been used to assess economic impacts of policies ( 57 , 60 , 76 ), to explore management scenarios reducing GHG emissions ( 56 , 77 ), and to determine the financial burdens of livestock diseases on farms ( 58 , 59 ). The FEPM model was run on two types of pig production systems in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…The FEPM is a modified version of ScotFarm, a farm level economic model developed at SRUC to conduct impact assessment of external shocks to an agricultural production system. The ScotFarm model has previously been used to assess economic impacts of policies ( 57 , 60 , 76 ), to explore management scenarios reducing GHG emissions ( 56 , 77 ), and to determine the financial burdens of livestock diseases on farms ( 58 , 59 ). The FEPM model was run on two types of pig production systems in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the financial impact of fascioliasis in 160 Scottish livestock farms with and without climate change, Shrestha et al (2020) found a 6% reduction in net profit on an average beef farm under standard disease conditions without the effects of climate change. When the effects of climate change were added, losses increased six-fold [77]. Clearly, climate change will have an impact on the profitability of cattle production.…”
Section: Beef Cattle Parasitism: Estimating Losses In a Changing Land...mentioning
confidence: 99%
“…Specifically, Schweizer et al [7] estimated a mean reduction of 9% in weight gain in growing cattle, a decrease in milk yield of 10% as well as a service period extended by 13 days, and an increase of 0.75 services per conception. According to recent work, the economic losses due to fasciolosis are likely to become even more pronounced when acknowledging climate change-induced effects and a higher proportion of herds possibly becoming exposed to F. hepatica [13]. Interestingly, notwithstanding the similar impact of fasciolosis across farms, some operations appear to be more capable of adjusting their systems and thus mitigating the impact of the disease, whereas others are more vulnerable to the adverse implications of fasciolosis [13].…”
Section: Introductionmentioning
confidence: 99%